ANALIS TERHADAP PASAL 409 UNDANG -UNDANG KESEHATAN TERKINI YANG MENIMBULKAN KONTROVERSI PERKEMBANGAN HUKUM PIDANA - Sukma Indah, Tashya; Nabilla Indrianny, Ika; Rendy, Muhammad (Jurnal Risalah Kenotariatan, 2023)
This journal aims to provide an in-depth analysis of the impact and controversy arising from the introduction and amendments to Article 409 of the recent Health Law. The primary focus of this research is on how this article influences and shapes the development of criminal law, particularly in the context of public health. This study employs a normative legal analysis method by thoroughly examining the text and substance of Article 409. Additionally, it incorporates a case study approach to understand its implementation in real-world situations. Controversies surrounding this article are discussed by considering diverse perspectives from legal experts, healthcare practitioners, and relevant community groups. By exploring these viewpoints, this research presents a comprehensive picture of both the positive and negative impacts of Article 409, as well as broader consequences on the criminal legal system. The research findings contribute to our understanding of legal changes related to health and lay the groundwork for more in-depth policy discussions. The conclusions and recommendations resulting from this research are expected to assist policymakers and legal practitioners in formulating more effective and equitable policies in the field of public health.